Pendidikan Perilaku Hidup Bersih dan Sehat (PHBS) Sebagai Upaya Meningkatkan Kesehatan Anak di SDN Langkob Desa Majalaya - Mayassa Fitri C; Ernie Halimatushadyah; Syafrima Wahyu; Frida Oktavia Punomo; Kartika Rahma (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
Clean and Healthy Living Behavior (PHBS) is a community service activity aimed at improving health status, especially for students in elementary schools. PHBS taught at an early age is needed to instill awareness of the importance of cleanliness as a way to maintain and improve personal and environmental health, especially schools. This Community Service is intended to provide understanding regarding PHBS material to students at SDN Langkob, Majalaya Village, Cianjur. In this activity, several appropriate methods will be applied to achieve the objectives, including the delivery of materials, assistance, independent practice related to PHBS, namely how to wash hands properly and correctly, as well as the provision of simple facilities. The results achieved in this activity include an increase in students' knowledge of the application of a clean and healthy lifestyle and the availability of simple hand washing facilities so that students and students can wash their hands in running water easily.